Early urea-to-creatinine ratio to predict rapid muscle loss in critically ill patients with sepsis: a single-center retrospective observational study - Jie Jiang; Hui Chen; Shan-shan Meng; Chun Pan; Jian-Feng Xie; Feng-Mei Guo (BMC Anesthesiology, 2025)
Abstract Background Patients with sepsis in the intensive care unit (ICU) often experience rapid muscle loss. The urea-to-creatinine ratio (UCR) is thought to reflect muscle breakdown (creatinine) and catabolism (urea) and is commonly used to assess nutritional and metabolic status. This study aimed to investigate whether changes in UCR (ΔUCR) can predict the development of rapid muscle loss in patients with sepsis. Methods This retrospective observational study was conducted in a university ICU between 2014 and 2021, involving adult patients (≥ 18 years) diagnosed with sepsis. The primary outcome was the incidence of rapid muscle loss during ICU hospitalization. Changes in the cross-sectional muscle area at the third lumbar vertebra (L3SMA) were measured using CT images to evaluate muscle loss. Rapid muscle loss was defined as a change in ΔL3SMA greater than 2% per day. Multivariable logistic regression was used to examine the association between UCR or ΔUCR and rapid muscle loss. The area under the receiver operating characteristic curve (AUC) was calculated to assess the predictive performance of UCR or ΔUCR for rapid muscle loss. Results Of the 482 patients, 141 (29.2%) experienced rapid muscle loss during their ICU stay. Multivariable logistic regression analysis revealed that ΔUCR was significantly associated with an increased risk of rapid muscle loss, with an odds ratio (OR) of 1.02 [95% CI: 1.01, 1.02]. The AUC for ΔUCR in predicting rapid muscle loss was 0.76 [95% CI: 0.68–0.83], with a threshold value of 19.4 µmol urea/µmol creatinine for ΔUCR. Conclusion The results demonstrate that ΔUCR is independently associated with rapid muscle loss in patients with sepsis and the AUC of the ROC curve for the ability of ΔUCR to predict rapid muscle loss was 0.76. Though additional prospective data are needed, our results suggest that ΔUCR may be useful in the early identification of critically ill patients with sepsis at risk of rapid muscle loss.